Does supplemental LH changes rate and time to ovulation and embryo yield in Santa Ines ewes treated for superovulation with FSH plus eCG? - Oliveira,Maria Emilia Franco (2012)
The objective was to evaluate if supplemental LH given at the end of FSH treatment would synchronize the time of ovulation and increase the ovulation rate and embryo yield in Santa Ines ewes. Twenty superovulatory (SOV) programs were accomplished in cross-over design (60d interval). On D0, a CIDR device was inserted, and the device was replaced with a new one 7 days later, when 37.5µg of d-cloprostenol was administered. On D12, we started the SOV treatment, administering 256mg of pFSH 8 times, 12h apart. On D14, the CIDR was removed, and 200IU of eCG and 37.5µg of d-cloprostenol were administered. On D15, the ewes were allocated into one of two groups, a Control group (n=10) that received no supplemental LH and a LH group (n=10) treated with 7.5mg of LH 24h after CIDR removal. Artificial inseminations (AI) were performed 42 and 48h after CIDR removal. The ovarian structures were evaluated by laparoscopy immediately before each AI and 5 days later (D21) when the embryos were collected. The LH ewes ovulated more frequently (P=0.05) before 42h than between 42 and 48h. Treatment with LH tended to increase the frequency of CL and to decrease the anovulatory follicles (P=0.08). The supplemental LH increased the frequency of ewes with a high SOV response (≥11 CL; P=0.05). In conclusion, supplemental LH increased the frequency of ewes with high SOV response and ovulating prior to 42h, however, there was no synchrony between ovulations. The supplemental LH also decreased the frequency of anovulatory follicles, although the ovulation rate and embryo yield were unaffected.